Driving Supply Chain Performance through Digitalization, Integration, and Resilience in Manufacturing Firms - Rama Anggara Putra; Nasar Buntu Laulita (Jurnal Manajemen dan Kewirausahaan, 2026)
Global complexities and operational disruptions pose significant challenges to modern logistics networks, making efficient supply chain management critical to firm survival. This study examines the impact of supply chain digitalization on supply chain performance. While digitalization is vital, its direct value remains debated; this research uniquely investigates how organizational integration and resilience simultaneously channel and maximize these digital benefits within a unified framework. A quantitative design was employed, using a structured survey administered to 297 experienced supply chain professionals at medium- and large-sized manufacturing firms in Batam City. The empirical findings reveal that supply chain digitalization directly boosts performance and yields significant indirect impacts through partial mediation. Specifically, digital adoption enhances supply chain integration, which in turn strengthens supply chain resilience, thereby ensuring operational stability and recovery capacity during crises. Implicationally, digital tools do not act in isolation but function as a technological backbone that requires integrated structures and resilient designs to unlock optimal value. It is highly recommended that logistics managers prioritize connective, cloud-based technologies and strategic partner collaboration rather than deploying isolated software solutions.